Efeito da rutina e da curcumina em marcadores inflamatórios e oxidativos em modelo experimental de hiperlipidemia - Manzoni, Alessandra Guedes (2019)
Hyperlipidemia is characterized by lipid abnormalities that result in inflammation and oxidative damage, factors involved in the development of atherosclerosis. Adenosine and adenosine deaminase (ADA) modulate immune and inflammatory responses as well as lipid metabolism. Curcumin and rutin are polyphenols with antioxidant, anti-inflammatory, and hypolipidemic potential. Thus, the objective of this study was to evaluate the activity of ADA in lymphocytes, platelets, neutrophils, and serum and the oxidative profile in liver and kidney of rats with induced hyperlipidemia, treated with curcumin and/or rutin. Adult Wistar male rats were pre-treated by gavage with rutin and/or curcumin for 30 days. Hyperlipidemia was acutely induced by intraperitoneal administration of Poloxamer-407 (P-407). After 36 hours, the animals were euthanized, and blood was collected for hemogram and serum and cell separation to evaluate enzymatic activity and biochemical parameters. The liver and kidney were collected to evaluate oxidative stress markers and antioxidant defense. P-407 induction increased levels of total cholesterol and triglycerides, reactive oxygen species (ROS), ADA and myeloperoxidase activity (MPO), and markers of oxidative damage in the liver, reduced antioxidant defenses and caused hematological changes. The pre-treatments prevented the increase in triglycerides, plasma MPO activity, ADA activity in serum and cells, oxidative stress in the liver and kidney, prevented the reduction of high-density lipid levels and antioxidant defenses in the liver and kidney, as well as reversing hematological parameters. Thus, positive effects of curcumin and/or rutin pre-treatments on the effects of hyperlipidemia were demonstrated, suggesting that their use as adjuvants may benefit patients with hyperlipidemia.